Epidemiology and antimicrobial resistance of toxin‐producing Klebsiella oxytoca clinical isolates from children admitted to the oncology chemotherapy center in Mofid Children's Hospital in Tehran, Iran: A cross‐sectional study - Nasim Sabzivand; Shiva Nazari; Fariba Shirvani; Leila Azimi; Siavash Salmanzadeh Ahrabi; Maedeh Mohammadi Estiri (Health Science Reports, 2024)
Abstract Background and Aims Klebsiella oxytoca (K. oxytoca) is the second bacterial cause of nosocomial infections in the general population after K. pneumoniae. This study surveyed the frequency of cytotoxin‐producing strains of K. oxytoca and their antibiotic susceptibility profile in a cohort of children admitted to a referral hospital with different malignancies. Methods The Stool samples of children admitted to the Cancer Chemotherapy Unit of the Mofid Children's Hospital, Tehran, Iran were analyzed using conventional biochemical tests and polymerase chain reaction targeting the pehX gene to identify K. oxytoca. The antibiotic susceptibility profile of isolated K. oxytoca against commonly prescribed antibiotics used in treating infection at the facility was determined using the Kirby–Bauer disk diffusion technique. Also, the prevalence of genes encoding toxins among K. oxytoca was identified by PCR assay. Results The Stool samples of 280 participants were taken for the study of which 38 samples [(55.3% (21/38) 42 males and 44.7% (17/38) females)] tested positive for various Klebsiella spp. Out of this, K. oxytoca was identified in 2.5% (7/280) stools using cultures and conventional biochemical tests. Also, the stools of 2.9% (8/280) of the participants tested positive for K. oxytoca using PCR assay. Using PCR, (2/7) of the K. oxytoca isolates tested positive for the npsA and npsB genes and were identified as toxigenic K. oxytoca strains. Conclusion The prevalence of toxin‐producing K. oxytoca strains in stool samples of children diagnosed with cancer in Iran is relatively low. Most of the K. oxytoca isolates were susceptible to tested antibiotics. Globally, active surveillance of toxigenic K. oxytoca strains in patients with different malignancies or immunocompromised patients is recommended in healthcare settings.